Pemanfaatan Pekarangan sebagai Dapur Hidup dan Gerakan Makan Telur sebagai Upaya Pengembangan Desa Oelomin Sadar Stunting - Ruliati, Luh Putu; Setyani, Ni Made Paramita; Sabat, Diana Meliani (Universitas Islam Nahdlatul Ulama Jepara, 2025)
Oelomin Village is one of the areas facing stunting problems. This condition requires serious attention, considering the long-term impacts that can be caused on the growth and development of children. The purpose of this activity was to provide knowledge about the education of the egg-eating movement to prevent stunting in toddlers and pregnant women, as well as the utilization of yards as a green fodder source for daily nutritional needs. The implementation method includes the preparation stage, implementation (counseling and practice), and evaluation which was attended by 20 members of the Sejahtera social assistance group at the Oelomin Village Office. The evaluation of the activity was carried out by filling out a questionnaire before and after the activity. The activity results showed an increase in participant knowledge of 63.23% regarding the education of the egg-eating movement, making compost from kitchen waste and organic waste, and developing a living kitchen. It can be concluded that the activity had been carried out well. However, there needs to be support and participation from partners and ongoing active assistance regarding stunting awareness, so that it can reduce the problem of stunting and improve the quality of life in Oelomin Village